John Symonds interviewed by David Ellyard - Symonds, John (John L.); Ellyard, David, 1942- (1980)
Symonds talks about Oliphant - his early impressions of when they were at college; his experiments with uranium and his first job with radio physics; his overseas scholarship and his work with Oliphant; he describes in detail the projects he was working on including the Birmingham Synchrotron.
Recorded on April 16, 1980 at Coogee, N.S.W.
Digital master available
John Symonds - nuclear physicist
Uncorrected transcript (typescript, 43 leaves) available.
Uncorrected transcript (typescript, 34 leaves)
Keywords: Symonds, John -- Interviews; Oliphant, Mark, -- Sir, -- 1901-2000.; Cyclotrons -- Great Britain -- Birmingham; Governors -- South Australia -- Biography; Physicists -- Australia -- Biography; Nuclear physics -- Research -- Australia; Science and state -- Australia